2005
DOI: 10.1080/08958370590922580
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Heme Oxygenase-1 in the Lungs of Rats Exposed to Crocidolite Asbestos

Abstract: Oxidative stress is thought to be the pathogenesis of pulmonary fibrosis induced by asbestos, and heme oxygenase-1 (HO-1) protects lung tissue against oxidative stress. We hypothesized that HO-1 is associated with oxidative lung injury caused by exposure to asbestos. This study was conducted to investigate the time course of HO-1 expression of lungs exposed to crocidolite asbestos in vivo. Male Wistar rats were administered 1 mg or 2 mg crocidolite asbestos suspended in saline by a single intratracheal instill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
12
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
3
12
0
Order By: Relevance
“…Increased HO-1 expression has also been reported in human interstitial pneumonia (UIP) 5) and cystic fibrosis (CF) 6) . Increased HO-1 expression has also been found in our study of a lung injury model in which rats were exposed to asbestos 7,8) and crystalline silica 9) ; therefore, HO-1 is thought to be related to lung injury caused by dust.…”
supporting
confidence: 67%
See 3 more Smart Citations
“…Increased HO-1 expression has also been reported in human interstitial pneumonia (UIP) 5) and cystic fibrosis (CF) 6) . Increased HO-1 expression has also been found in our study of a lung injury model in which rats were exposed to asbestos 7,8) and crystalline silica 9) ; therefore, HO-1 is thought to be related to lung injury caused by dust.…”
supporting
confidence: 67%
“…Therefore, the expression of protein (concentration of HO-1 protein / protein exactly) was increased from the acute phase as an acute inflammatory reaction. We have also reported that more alveolar macrophages were stained for HO-1 in rats exposed to crocidolite, chrysotile and crystalline silica compared with the control groups [7][8][9] . Maestrelli et al reported that HO-1-positive macrophages were increased in smokers with chronic obstructive pulmonary disease (COPD) as compared with nonsmoking subjects in an immunohistochemistry study of human lung surgical specimens 13) .…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Hemoglobin metabolism is mediated by heme oxygenase-1, which is upregulated when animals or cells are treated with asbestos. (68,69) Therefore, this Refer to Table S1 for details.…”
Section: Discussionmentioning
confidence: 99%